2017
DOI: 10.1016/j.neuroimage.2015.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive neuroscience neuroimaging repository for the adult lifespan

Abstract: With recent advances in neuroimaging technology, it is now possible to image human brain function in vivo, which revolutionized the cognitive neuroscience field. However, like any other newly developed techniques, the acquisition of neuroimaging data is costly and logistically challenging. Furthermore studying human cognition requires acquiring a large amount of neuroimaging data, which might not be feasible to do by every researcher in the field. Here, we describe efforts in our group to acquire one of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…The in‐scanner tasks included 11 cognitive tasks that were previously found to cluster into four primary reference abilities (Salthouse, 2009; Salthouse & Ferrer‐Caja, 2003): vocabulary (VOCAB: synonyms and antonyms), perceptual speed (SPEED: digit symbol, letter comparison, pattern comparison), fluid reasoning (FLUID: paper folding, matrix reasoning, and letter sets), and episodic memory (MEM: logical memory, word order, and paired associates). These tasks have been used extensively in previous studies conducted by the authors of the current study; for detailed information on these tasks, please see (Razlighi et al., 2017; Stern et al., 2014; Varangis, Razlighi, et al., 2019). One task, the Picture Naming task from the VOCAB reference ability, was not included in the present analyses due to in‐scanner motion arising from participants speaking their responses aloud during the scanned task.…”
Section: Methodsmentioning
confidence: 99%
“…The in‐scanner tasks included 11 cognitive tasks that were previously found to cluster into four primary reference abilities (Salthouse, 2009; Salthouse & Ferrer‐Caja, 2003): vocabulary (VOCAB: synonyms and antonyms), perceptual speed (SPEED: digit symbol, letter comparison, pattern comparison), fluid reasoning (FLUID: paper folding, matrix reasoning, and letter sets), and episodic memory (MEM: logical memory, word order, and paired associates). These tasks have been used extensively in previous studies conducted by the authors of the current study; for detailed information on these tasks, please see (Razlighi et al., 2017; Stern et al., 2014; Varangis, Razlighi, et al., 2019). One task, the Picture Naming task from the VOCAB reference ability, was not included in the present analyses due to in‐scanner motion arising from participants speaking their responses aloud during the scanned task.…”
Section: Methodsmentioning
confidence: 99%
“…Both RANN and CR studies have been approved by the Institutional Review Board of Columbia University. More detailed information about the 2 studies can be found in previous publications (Habeck et al, 2016(Habeck et al, , 2017Razlighi et al, 2017;Stern, 2009Stern, , 2012Stern et al, 2014). We selected participants who had complete data on the measures used in the current analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The cognitive variables included in this study are comprised of their performance on tasks completed during the fMRI scan. The in-scanner tasks were designed to measure performance within each of the four reference abilities: vocabulary (VOCAB: synonyms and antonyms), perceptual speed (SPEED: digit symbol, letter comparison, pattern comparison), fluid reasoning (FLUID: paper folding, matrix reasoning, and letter sets), and episodic memory (MEMORY: logical memory, word order, and paired associates) (for further information on tasks please see Razlighi, Habeck, Barulli, & Stern, 2017; Stern et al, 2014). In the vocabulary domain, the synonyms and antonyms tasks required participants to select a synonym/antonym (respectively) for a selected word from among four different options displayed on the same screen (15 trials per task).…”
Section: Methodsmentioning
confidence: 99%